2024
DOI: 10.3390/jcm13061603
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Manifestations of Syphilis: A 10-Year Retrospective Study

Giulia Ciccarese,
Antonio Facciorusso,
Mario Mastrolonardo
et al.

Abstract: Background: The incidence of syphilis has increased in high-income countries in the past few decades, especially among men who have sex with men. In the present study, we aimed to analyze the correlations between atypical syphilis manifestations and the demographic, clinical, and laboratory features of patients and to review unusual presentations of syphilis reported in the literature. Methods: We conducted a retrospective analysis of 307 patients with syphilis diagnosed between 1 January 2013 and 31 October 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…The recent studies cited found that atypical manifestations of syphilis were statistically correlated with syphilis reinfection, especially annular lesions. 11 , 12 Moreover, the presence of atypical manifestations of syphilis could be related to the circulation of different strains of T. pallidum . 13 The possibility of recurrent rash as reinfection of T. pallidum was considered based on our patient’s previous infection treatment and the medical history of her sexual partner.…”
Section: Discussionmentioning
confidence: 99%
“…The recent studies cited found that atypical manifestations of syphilis were statistically correlated with syphilis reinfection, especially annular lesions. 11 , 12 Moreover, the presence of atypical manifestations of syphilis could be related to the circulation of different strains of T. pallidum . 13 The possibility of recurrent rash as reinfection of T. pallidum was considered based on our patient’s previous infection treatment and the medical history of her sexual partner.…”
Section: Discussionmentioning
confidence: 99%